Synthesis and in vitro phototoxicity of multifunctional Zn(II)meso-tetrakis(4-carboxyphenyl)porphyrin-coated gold nanoparticles assembled via axial coordination with imidazole ligands - Alea-Reyes, Maria E.; Penon, Oriol; García Calavia, Paula; Marín, María J.; Russell, David A.; Pérez-García, Lluïsa (Elsevier, 2018)
Hypothesis